The Contemporary Belarusian Dialects in Eastern Lithuania (Regions of Ignalina and Švenčionys) - Jankowiak, Mirosław (Slavistica Vilnensis, 2017)
The aim of the article is to present contemporary Belarusian dialects functioning in Eastern Lithuania (in the regions of Ignalina and Švenčionys), which have not been the subject of comprehensive linguistic research. The basis for the analysis are the author’s own materials, which were collected during field research in 2014-2016. The structure of these Belarusian dialects (selected features in phonetics, morphology, syntax, vocabulary and phraseology) as well as the sociolinguistic aspect of their functioning in a multilingual environment are demonstrated in the article.